Buckled-type valves integrated by parylene micro-tubes - Yang, Lung-Jieh; Wang, Hsin-Hsiung; Wang, Jiun-Min; Liu, Kuan-Chun; Ko, Kai-Chung (Sensors and actuators. A. Physical., 2006)
This paper demonstrates a newly developed parylene buckled-type valve with the same working principle of the “buckled straw”. Such a new design of the valve uses the buckled region of plastic tubes as the on/off switch for flow control, and there is no need of adding deformable diaphragms or sealing parts into the valve device. By the merit of its concise mechanism, i.e., a straight pipeline with the region for buckling, the buckled-type valve intrinsically operates with almost zero dead volume. The fabrication sequence of this new valve combines the techniques of sacrificial mould of capillary glass tubes, conformal parylene coating and SU-8 photolithography. A valve device of 1 cm long, 0.8 cm wide and with the buckled micro-tube of 390 μm outer-diameter is demonstrated. The turn-on (flow-closing) angle of this valve verified as 120° experimentally.